(untitled) (Huellas, 2023)
The objective of this article is to identify and analyze the changes of residence of the popular sectors of Gran San Miguel de Tucumán based on three dimensions: the location of the target neighborhood, the residential trajectories and strategies implemented, and the characteristics of the housing. The Los Vásquez neighborhood was taken as a case study, located towards the southeast of the agglomerate, in one of the most degraded areas with poor environmental conditions of the city, in an environment characterized by the presence of popular settlements with high levels of informality, vulnerability and poverty. The study of changes in residence in relation to different socio-spatial variables provides insight into the dynamics of the social division of space. While groups with sufficient economic income can choose the location and type of housing, vulnerable sectors are faced with multiple limitations to meet their housing needs imposed, above all, by the labor, land and housing markets. The reconstruction of changes in the residence of the popular sectors made it possible to build a baseline and rethink urban policies with the aim of achieving greater equality among people and equitable access to the city.